Optimization Methods and Food Safety Consideration of Edible Film: A Mini Review - Delima, Meita Putri; Widjanarko, Simon Bambang; Mahatmanto, Tunjung (The Journal of Experimental Life Science, 2025)
Conventional food packaging plastics harm the environment due to their non-biodegradability, resulting in the accumulation of microplastics. Edible films present an eco-friendly packaging alternative capable of extending the shelf life of food products. These biodegradable films may be derived from natural biopolymers such as proteins, polysaccharides, and lipids. This mini-review explores the optimization techniques for edible film production and their safety in food applications. The information may be used to select effective optimization methods and appropriate safety tests for edible film formulation. Optimization methods, like Central Composite Rotatable Design (CCRD), may enhance the properties of edible films and reduce production costs effectively. However, studies advise against using mixture designs for edible films containing more than three ingredients. To ensure safety, edible films must be made using materials that are Generally Recognized as Safe (GRAS) and comply with regulatory standards set by the Food Drug Administration (FDA). From an applied perspective, toxicity tests (in vitro or in vivo) may be performed to evaluate the health implications of edible films and offer a more comprehensive view of their benefits and limitations in food packaging. Keywords: Edible Film, Food Safety, Optimization method.